STIMULASI PERTUMBUH KEMBANGAN BAYI, BALITA SERTA ANAK PRASEKOLAH - siti kholifatul marhamah; Arum Dwi Anjani; Selawati Selawati; Devy Lestari Nurul Aulia; Nursai’dah Nursai’dah; Hanik Rosida; Vitra Vica (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Development is a qualitative functional change in both physical and mental functions as output of its association with environmental effects. Child development could be optimized in case the interaction is fits the needs of the child at many stages of development, eventhought the baby was not born yet. Also the right stimulation would stimulate toddler's brain to construct ability to move, speak, language, and independence in toddlers. Early test of growth and development problems could be done so we could identify toddler growth and development problem earlier, along with any complaints from parents towards their child's growth and development. The stimulation factors become more crucial towards child's development. Parental stimulation towards child development is a step implied in an ongoing interaction activity among parents with children to construct a great relationship, and facilitate children to construct their capabilities which include the development of great motor, gross motor, language also social capabilities based on the stage development. However, this research method uses searching for analytical data by using literature reviews or reviews by looking for journals or articles that are relevant to the stimulation of the growth also development of babies, toddlers and preschool children. The population in this study were babies, toddlers and preschoolers who were experiencing a period of growth and development. Therefore babies, toddlers and preschoolers should be based on their developmental activities so parents could observe also stimulate development based on their ages.